ANALISIS PERMINTAAN KONSUMEN TERHADAP LAYANAN TRANSPORTASI ONLINE DI KOTA MALANG - Ratna Sari, Sonia (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2024)
This research aims to measure the extent of consumer demand changes for online transportation services in Malang City following a tariff increase and to identify the factors influencing the demand for these services. This research utilized a quantitative approach and was analyzed through the wilcoxon test and multiple linear regression analysis. The findings reveal significant changes in consumer demand after the tariff hike. Specifically, the variable of online transportation service tariffs shows a positive and significant influence. Income demonstrates a positive but insignificant effect, while the variables of conventional transportation services tariffs and travel speed each indicate a negative influence that is not significant and significant, respectively, on the demand for online transportation services. Based on these findings, it is crucial for online transportation service companies to maintain comfort and security, as these factors are top priorities for consumers in choosing transportation services. Additionally, the government can contribute to maintaining operational stability for companies, ensuring safety for users, and overall stability in the transportation ecosystem.